Prevalence and prognostic impact of hsCRP elevation are age‐dependent in women but not in men undergoing percutaneous coronary intervention. Issue 7 (25th November 2020) - Blum, Moritz; Cao, Davide; Chandiramani, Rishi; Goel, Ridhima; Roumeliotis, Anastasios; Sartori, Samantha; Beyhoff, Niklas; Kelle, Sebastian; Kovacic, Jason C; Krishnan, Prakash; Sweeny, Joseph; Barman, Nitin; et al.
Abstract: Background: High‐sensitivity C‐reactive protein (hsCRP) predicts outcomes after percutaneous coronary intervention (PCI). Objective: We studied the prevalence and prognostic impact of hsCRP elevation according to age in men and women undergoing PCI. Methods: We included patients undergoing PCI at our center from 2010 until 2017, excluding those with myocardial infarction (MI) on presentation, neoplastic disease and hsCRP >10 mg/L at baseline. Elevated hsCRP was defined as >3 mg/L. The outcome of interest was major adverse cardiac events (MACE) consisting of all‐cause death, MI and target vessel revascularization. The association between hsCRP elevation and outcomes was assessed using adjusted Cox models. Results: 10, 432 men and 4, 345 women were included. Elevation of hsCRP was present in 25.7% of men and 37.0% of women ( p  < .01). In men, prevalence of hsCRP elevation was stable across age strata ( ptrend  = .42). In women, hsCRP elevation was most prevalent in patients <50 years (44.6%) and decreased stepwise with increasing age ( ptrend  < .001). After stratifying the population into age quartiles (Q1: <59 years, Q2: 59–66 years, Q3: 67–74 years, Q4: ≥75 years), hsCRP elevation was associated with increased risk of MACE across all age groups in men (HR [95% CI] Q1: 1.49 [1.12–1.98]; Q2: 1.51 [1.21–2.06]; Q3: 1.76 [1.27–2.51]; Q4: 1.43[1.03–1.97]). In women, hsCRP elevation was associated with increased risk of MACE only among older patients (HR [95% CI] Q1: 1.08 [0.64–0.82]; Q2: 1.52 [0.93–2.46]; Q3: 1.65 [1.08–2.50]; Q4: 1.52 [1.02–1.28]). Conclusion: Among patients undergoing PCI, prevalence and prognostic value of hsCRP elevation were age‐dependent exclusively in women.